PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KARTU AS - Hidayatullah, Mohammad Nauval (Arthavidya Jurnal Ilmiah Ekonomi, 2020)
Abstract: The purpose of this study was to determine the effect of the promotion mix consisting of advertising (X1), personal selling (X2), sales promotion (X3), and public relations (X4) both simultan and partial on purchasing decisions (Y) and also to find out the promotion mix of the biggest variable influence on US cellular card student students, Faculty of Economics and Business, Airlangga University. The population of this research is students of the Faculty of Economics and Business, Airlangga University. The method used in this study was purposive sampling, by 50 respondents and the study was conducted in December 2016 The data collecting methode were collecting kuesioner and library research. The Data Processing technique was used software of SPSS version 16.0 windows used scale of likert. The result of this research from F test (Simultan) proved the advertising (X1), personal selling (X2), sales promotion (X3), and public relations (X4) had an signifikan effect towards purchase decision (Y) of college students user AS card cellular at Economics and Business Faculty Airlangga University. It can be concluded from the fourth independent variable which has the biggest influence on purchasing decisions (Y) US mobile card user students at the Faculty of Economics and Business, Airlangga University are personal selling (X2). Keyword(s): Promotion mix and Purchase Decision